Clinicopathological features of atypical membranous nephropathy with unknown etiology in adult Chinese patients. Issue 32 (August 2018) - Jiang, Zhenbin; Cai, Meishun; Dong, Bao; Yan, Yu; Yang, Bing; Wang, Mi; Wang, Yan; Li, Xin; Lian, Lichao; Li, Song; Zuo, Li
Abstract : Abstract: Membranous nephropathy is typically classified as idiopathic and secondary, but nowadays the number of atypical membranous nephropathy (aMN) is increasing, many of which cannot determine its etiology in China. In this study, we compared the clinical and pathological characteristics of idiopathic membranous nephropathy (iMN) with aMN with unknown etiology from a single center in China. We retrospectively reviewed the clinical data of 577 patients with iMN and aMN at Peking University People's Hospital from January 2006 to December 2015 over a 10-year period, and analyzed their clinical and pathological characteristics. The level of serum phospholipase A2 receptors (PLA2R) antibody was detected in 106 iMN and 162 aMN patients. There were 278 iMN patients and 299 aMN patients who were included into this study in 3210 cases of renal biopsy during a 10-year period in our hospital. The average age of patients with iMN was significantly older than those with aMN (54.77 ± 13.01 vs 47.13 ± 16.16, P <  .001). Around 75 patients (27%) were smokers in iMN patients, and 111 patients (37.1%) in aMN patients ( P =  .009). The mainly clinical manifestation of these 2 groups was nephrotic syndrome (61.5% in iMN group vs 58.4% in aMN group), but there were more patients accompanied with nephritis syndrome in aMN group than iMN group (17.1% vs 6.1%, P <  .001). The immunofluorescence of renal biopsy showed "full house" in aMN group; and IgG subclass of the glomeruli demonstrated IgG4 (90.4%) was commonest in iMN group, but IgG1 (94.6%) in aMN group. 51 (48.1%) patients with iMN were detected positive PLA2R antibody in their serum, and 93 (57.4%) in aMN patients ( P =  .168). The patients with positive PLA2R antibody had higher positive rate of microscopic hematuria and urinary protein, lower albumin. The aMN patients are younger, higher smoking rate, its main clinical manifestation is nephrotic syndrome, but more of them accompanied with nephritis syndrome than those in iMN patients. Serum PLA2R antibody could not distinguish aMN from iMN. aMN could be a special glomerular disease in China, and need a further research on a larger scale.